Common Fixed Points of Set-Valued Mappings in Hyperconvex Metric Spaces - Jorquera-Alvarez, E (Birkhauser Verlag AG, 2018)
In this paper, we establish several common fixed point theorems for families of set-valued mappings defined in hyperconvex metric spaces. Then we give several applications of our results. © 2018, Springer International Publishing AG, part of Springer Nature.